Synthesis, Characterization and Biological Evaluation of New 4-Aryl-6-(2,5-dichlorothiophen-3-yl)-1,2-dihydro-2-oxopyridine-3-carbonitrile - Al-Refai, Mahmoud (Asian Journal of Chemistry, 2015)
Condensation of 3-acetyl-2,5-dichlorothiophene with different aldehydes in presence of ethyl cyanoacetate led to the formation of the new oxopyridine derivatives containing a thiophene moiety (3a-j) in high yields. All newly synthesized compounds were characterized by standard spectroscopic techniques. Antibacterial evaluation for all new compounds shows no activity against four different types of bacteria.